ISOLATION AND CHARACTERIZATION OF LACTOBACILLUS ISOLATED FROM MILK, CURD AND FECAL SAMPLE AND ASSIGNING THEIR PROBIOTIC VALUES - POONAM B CHAUHAN; POONAM B CHAUHAN; DIVYA DARU (International Journal of Pharma and Bio Sciences, 2016)
Probiotics are ‘nonpathogenic’ live microbial, mono or mixed culture preparations, which, when applied to humans or animals in high enough doses, benecitially affect the host by improving the intestinal microbial balance and it’s properties. The most widely used bacteria considered as probiotics are lactobacillus and bifidobacterium. In present study a total of 14 Lactobacillus isolates were isolated from milk, curd and fecal sample of newborn baby. The strains were characterized as Lactobacilli on the bases of their morphological and physiological characteristics. Probiotic properties were examined including tolerance to acid and bile, antibiotic resistance etc. In probiotic properties, these strains were resistant to both acid and bile. Antimicrobial activity of the probiotic Lactobacillus was determined by well diffusion method. It was concluded that out of 14 Lactobacillus strains 5 showed the potential probiotic value.